Alasan Amerika Serikat Keluar Dari WHO Pada Saat Pandemi Covid 2020 - Solikah, Nining; Ismiatun, Ismiatun (Kajian Hubungan Internasional, 2023)
This study aims to analyze the reasons for the United States leaving the WHO during the COVID-19 pandemic in 2020 and focuses on the United States' foreign policy. This thesis research is qualitative descriptive with descriptive analysis method. This research uses documentation data collection techniques with secondary data sources. Researchers collected data from various sources from news and other media documentation regarding the spread of covid 19 in 2019. And the policies of the United States president Donald Trump who made contradictory policies in the midst of the covid 19 pandemic. Trump qualifies to be classified as a risk-prefering type leader or willing to choose certain policies that have a high level of risk. During the Covid-19 period, which began in December 2019 and has continued until now, has infected as many as 13.5 million people in 188 countries (data as of mid-July 2020), global geopolitical competition does not show a tendency to subside either. Even China and the United States are actually involved in accusing each other and fighting propaganda about the origin of the virus. The conflict then escalated to the cutting stage. The United States is now the largest funding country for WHO. Deputy assistant secretary of state for international organizations Nerissa Cook said while at the White House that the WHO needed reforms and that it started by demonstrating its independence from the Chinese Communist Party. Nerissa Cook also said the United States wanted greater transparency and accountability with the WHO. He hopes that there will be a change in WHO management so that it focuses more on prevention and detection of the COVID-19 pandemic.